Professional C programming LiveLessons - Seacord, Robert C. (LiveLessons (Indianapolis, Ind.), 2013)
"Professional C Programming LiveLessons, Part I: Writing Robust, Secure, and Reliable Code by Robert C. Seacord provides an in depth explanation of how to use common C language features to produce robust, secure, and reliable code. The video is designed for developers who have completed an introductory course in C language programming. In six lessons, Professional C Programming, Part I shows developers how to perform common C language programming tasks correctly while avoiding programming errors that are not always detected or reported by the compiler."--Resource description page.